2021
DOI: 10.1007/s00420-021-01718-7
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying increases the risk of anxiety through a stress-induced β2-adrenergic receptor mechanism: a multisource study employing an animal model, cell culture experiments and human data

Abstract: Objectives Several studies show that severe social stressors, e.g., in the form of exposure to workplace bullying in humans, is associated with negative mental health effects such as depression and anxiety among those targeted. However, the understanding of the underlying biological mechanisms that may explain the relationship between exposure to bullying and such negative health outcomes is scarce. The analyses presented here focus on understanding the role of the β2-adrenergic receptors (ADRB2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…The difference between the data of mice and rats could be related to minor differences in the handling of the animals and the resident-intruder protocol, and a suggestion for standardized protocol has recently been published (Munshi et al, 2022). Anyhow, when we previously examined the SPD rats 24 h after the last stress exposure to discover persistent effects on social behavior or weight gain, we did not observe any ''resilient'' group based on social avoidance among the stress-exposed rats (Jacobsen et al, 2020;Rajalingam et al, 2021), as might be expected if we had carried out the experiment in inbreed mice (Nasca et al, 2019).…”
Section: Social Stress Induces Pituitary Epigenetic Changesmentioning
confidence: 92%
See 2 more Smart Citations
“…The difference between the data of mice and rats could be related to minor differences in the handling of the animals and the resident-intruder protocol, and a suggestion for standardized protocol has recently been published (Munshi et al, 2022). Anyhow, when we previously examined the SPD rats 24 h after the last stress exposure to discover persistent effects on social behavior or weight gain, we did not observe any ''resilient'' group based on social avoidance among the stress-exposed rats (Jacobsen et al, 2020;Rajalingam et al, 2021), as might be expected if we had carried out the experiment in inbreed mice (Nasca et al, 2019).…”
Section: Social Stress Induces Pituitary Epigenetic Changesmentioning
confidence: 92%
“…We have recently demonstrated that repeated social defeat (the resident-intruder paradigm) is a strong stressor that may induce behavioral changes associated with reduced weight gain and increased impulsivity or locomotion 24 h after the last experience of social defeat in rats (Jacobsen et al, 2020;Rajalingam et al, 2020). A correlation between reduced social behavior and increased plasma (nor)epinephrine in animals exposed to social stress has also been observed (Rajalingam et al, 2021). Thus, it seems plausible that such social stressors, i.e., the asymmetry of power (Rajalingam et al, 2020), may trigger long-term changes in the hypothalamus-pituitary-adrenal (HPA) axis and subsequent stress-related biological processes underlying fear and nervousness (Smith and Vale, 2006).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…When this psychological pain reaches the threshold of an individual, it can lead to suicide (Shneidman, 1993 ). In addition, repeated exposures to workplace bullying may cause a series of neuroendocrine and immunological changes, including increased activity of the hypothalamic–pituitary–adrenal axis and sympathetic nervous system (Reader et al, 2015 ; Rajalingam et al, 2021 ). Such repeated exposures may also elevate inflammatory markers (Jacobsen et al, 2018 ; Rajalingam et al, 2020 ), which may facilitate individual engagement in suicide ideation and attempts (Ernst et al, 2009 ; Van Heeringen & Mann, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Workplace bullying results in depression, anxiety, low levels of self-esteem, and feelings of incompetence (Bernstein and Batchelor, 2002). In addition, workplace bullying has the capacity to trigger a neuro-immune mechanism causing severe anxiety and psychological consequences (Rajalingam et al, 2021), mental distress (Nielsen et al, 2020), insomnia (Nielsen et al, 2021), emotional exhaustion (Anasori et al, 2020), and psychological and post-traumatic stress disorders (Chenevert et al, 2022;Hong et al, 2022). Equivalently, the detrimental effects of bullying on organizational performance are significant.…”
Section: Introductionmentioning
confidence: 99%